2015
DOI: 10.1007/s10753-015-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a-5p Antagonized AGEs- and P.g-LPS-Induced ABCA1 and ABCG1 Dysregulation in Macrophages via IRAK-1 Downregulation

Abstract: The miR-146-mediated IL-1 receptor-associated kinase 1 (IRAK-1) feedback circuit has been shown to inhibit inflammatory response in macrophages against lipopolysaccharide (LPS). The aim of this study is to compare the antagonized effects of miR-146a-5p on Porphyromonas gingivalis (P.g) lipolysaccharide (LPS)- and advanced glycation end products (AGEs)-triggered ABCA1 and ABCG1 dysregulation and explore the underlying mechanism. THP-1-derived macrophages transfected with miRNA mimics or not were treated with P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…To further investigate the functional role of miR‐146a in CAP, we analyzed miR‐146a expression in P. endodontalis LPS‐treated MC3T3‐E1 cells. Similarly, we also found that miR‐146a expression was statistically increased in P. endodontalis LPS‐treated cells in a dose‐dependent manner, which was in good agreement with previous studies, showing an increase in the miR‐146a response to LPS stimulation . These data imply that miR‐146a might contribute to immuno‐inflammatory responses in CAP.…”
Section: Discussionsupporting
confidence: 92%
“…To further investigate the functional role of miR‐146a in CAP, we analyzed miR‐146a expression in P. endodontalis LPS‐treated MC3T3‐E1 cells. Similarly, we also found that miR‐146a expression was statistically increased in P. endodontalis LPS‐treated cells in a dose‐dependent manner, which was in good agreement with previous studies, showing an increase in the miR‐146a response to LPS stimulation . These data imply that miR‐146a might contribute to immuno‐inflammatory responses in CAP.…”
Section: Discussionsupporting
confidence: 92%
“…MiR‐155 promotes M1 polarization of macrophages though the CCAAT/enhancer binding protein (C/EBP‐β) signaling cascade (Figure ) . MiR‐146 has a robust anti‐inflammatory role, and it favors M2 phenotype through targeting TNF receptor‐associated factor (TRAF)‐6, interleukin‐1 receptor‐associated kinase (IRAK1), STAT‐1, and TLR4 …”
Section: Mechanisms Whereby Melatonin Regulates Macrophage Polarizationmentioning
confidence: 99%
“…65,181,182 MiR-146 has a robust anti-inflammatory role, and it favors M2 phenotype through targeting TNF receptor-associated factor (TRAF)-6, interleukin-1 receptor-associated kinase (IRAK1), STAT-1, and TLR4. [183][184][185] Melatonin modulates the expression of miRNAs, [186][187][188] effects that are meanwhile amply documented and gain increasing attention. Insofar, it is not surprising that melatonin can alter the macrophage polarization status via regulating miRNAs.…”
Section: Melatonin Shapes Macrophage Polarization Through Mirnasmentioning
confidence: 99%
“…Li et al [23] reported that levels of miRNA-146a-5p were significantly elevated in macrophages 24 h after stimulation with a high dose of P. gingivalis LPS or an equivalent immunogen. The pro-inflammatory P. gingivalis LPS may participate in triggering dysregulation of the cassette transporters ABCA1 and ABCAG1 during periodontitis.…”
Section: Possible Functions For Mirna-146 and Mirna-155 In Periodontitismentioning
confidence: 99%
“…This demonstrates a potential therapeutic potential of candidate miRNA for dyslipidemic subjects. Li et al [23] suggested that in macrophages, miRNA-146a can operate as an inflammatory brake on LPS stimulation by decreasing the levels of two adapter proteins (IRAK1 and TRAF6) in an NF-κB-dependent manner [26], implying a strong therapeutic potential for miRNA-based therapies.…”
Section: Possible Functions For Mirna-146 and Mirna-155 In Periodontitismentioning
confidence: 99%